Pathogens of peritoneal dialysis peritonitis: Trends from a single-center experience over 15 years - Tae Yeon Hwang; Myung Gyu Kim; Se Won Oh; Sang-Kyung Jo; Won-Yong Cho; Jihyun Yang (The Korean Society of Nephrology, 2020)
Background : Concerns are increasing about the emergence of pathogens with antibiotic resistance in peritoneal dialysis (PD) peritonitis. We investigated the current pathogen trends and risk factors in PD peritonitis. Methods : We conducted a retrospective study analyzing data from 643 patients who maintained PD over 3 months between January 2001 and December 2015. The isolated pathogens from PD peritonitis were compared between period A (2001-2008) and period B (2009-2015). Results : Among 643 PD patients, 252 patients experienced one or more episodes of PD peritonitis (total 308 episodes) during the median follow-up of 66 months. In both periods, gram-positive bacteria were the dominant pathogens (22.2% vs. 53.8%, P < 0.01). Gram-negative bacteria showed an increasing tendency in period B, but without statistical significance (17.0% vs. 23.7%, P = 0.15). The culture-negative rate was improved from 57% in period A to 18% in period B (P < 0.01). There was no increase in the prevalence of resistant pathogens such as methicillin-resistant Staphylococcus epidermidis (MRSE), Staphylococcus aureus (MRSA) and extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli between periods A and B. Preserved residual renal function was associated with a lower risk of PD peritonitis (odds ratio, 0.53; 95% confidence interval, 0.31-0.88; P = 0.01). Conclusion : Over the past two decades, the pathogens of PD peritonitis have not significantly changed in Korea. Gram-positive organisms remained dominant, with S. epidermidis being the most common pathogen. Resistant bacteria such as MRSE, MRSA, ESBL-producing Gram-negative bacilli did not increase, but should be monitored.